EFEKTIVITAS METODE PEMBELAJARAN TIPE STAD DALAM KETERAMPILAN MEMBACA PEMAHAMAN (DOKKAI 3) - Afri Damayanti; Hermandra Hermandra; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the aim of this study is to see reading comprehension skills Dokkai after using the method of Students Teams Achivement Divisions (STAD). In this study using weak experiment with one group pretest posttest design type. The object number of samples in this are 23 students from B class Department of Japanese Language Education Riau University academic year 2017. Sampling technique is using purposive sampling. In this study two tests were applied, there are pretest and posttest. The result of the pretest and posttest were processed using by Wilcoxon Sign Rank Test on SPSS 24 softwere. The average pretest value obtained by students increased to 78. Therefore, STAD type learning method is effectively used in improving reading comprehension skills Dokkai on B class student Departement of Japanese Language Education Riau university academic 2017.Key Words: Dokkai, Cooperative Learning type STAD, Reading Comprehension